1999
DOI: 10.1097/00000542-199905000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Response of Caudal Ropivacaine in Children 

Abstract: Ropivacaine is well tolerated and provides effective analgesia when given for caudal blockade in small children for inguinal hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 23 publications
5
67
0
2
Order By: Relevance
“…15 Although ropivacaine at low concentrations may be suitable for providing postoperative analgesia, as shown for outpatient hernia surgery performed under spinal anesthesia, 4 higher concentrations are required for effective surgical anesthesia. 1,16,17 The high concentrations used in this study provided both surgical anesthesia and postoperative analgesia, with pain relief significantly outlasting soft tissue numbness.…”
Section: Discussionmentioning
confidence: 98%
“…15 Although ropivacaine at low concentrations may be suitable for providing postoperative analgesia, as shown for outpatient hernia surgery performed under spinal anesthesia, 4 higher concentrations are required for effective surgical anesthesia. 1,16,17 The high concentrations used in this study provided both surgical anesthesia and postoperative analgesia, with pain relief significantly outlasting soft tissue numbness.…”
Section: Discussionmentioning
confidence: 98%
“…Seventeen such RCTs were reviewed in detail using a structured methodology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Two review articles were also identified. 18,19 The reference lists for all of these 19 publications were reviewed to identify any further RCTs that may have been missed with the initial search strategy; no such study was found.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, it appears that most of the studies (with two notable exceptions) included in this evidence-based clinical update compared ''nearly'' equipotent doses of the drugs. 5,17 This then represents a slight weakness in the methodology of most of the studies reviewed.…”
Section: Comment On Relative Potencymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 La ropivacaïne 0,5 % n'est pas utilisée en clinique courante alors que ses caractéristiques pharmacologiques sont décrites chez l'enfant de plus de un an: à la posologie de 0,75 mlÁkg (0,375 mgÁkg -1 ) elle assure une analgésie d'une durée proche de 24 h, un bloc moteur de plusieurs heures avec des concentrations plasmatiques inférieures à celles considérées comme étant toxiques chez l'adulte. 5 Ces caractéristiques, qui correspondaient à nos impératifs chirurgicaux, nous a permis de réduire l'anesthésie à une simple sédation prolongée.…”
Section: Au Rédacteur En Chefunclassified